Relationship between hospital performance measures and outcomes in patients with acute ischaemic stroke: a prospective cohort study. Issue 7 (1st August 2018) - Zhang, Xinmiao; Li, Zixiao; Zhao, Xingquan; Xian, Ying; Liu, Liping; Wang, Chunxue; Wang, Chunjuan; Li, Hao; Prvu Bettger, Janet; Yang, Qing; Wang, David; Jiang, Yong; et al.
Abstract : Objective: Evidence-based performance measures have been increasingly used to evaluate hospital quality of stroke care, but their impact on stroke outcomes has not been verified. We aimed to evaluate the correlations between hospital performance measures and outcomes among patients with acute ischaemic stroke in a Chinese population. Methods: Data were derived from a prospective cohort, which included 120 hospitals participating in the China National Stroke Registry between September 2007 and August 2008. Adherence to nine evidence-based performance measures was examined, and the composite score of hospital performance measures was calculated. The primary stroke outcomes were hospital-level, 30-day and 1-year risk-standardised mortality (RSM). Associations of individual performance measures and composite score with stroke outcomes were assessed using Spearman correlation coefficients. Results: One hundred and twenty hospitals that recruited 12 027 patients with ischaemic stroke were included in our analysis. Among 12 027 patients, 61.59% were men, and the median age was 67 years. The overall composite score of performance measures was 63.3%. The correlation coefficients between individual performance measures ranged widely from 0.01 to 0.66. No association was observed between the composite score and 30-day RSM. The composite score was modestly associated with 1-year RSM (Spearman correlation coefficient, 0.34; p<0.05). The composite score explained only 2.53% and 10.18% of hospital-level variation in 30-day and 1-year RSM for patients with acute stroke. Conclusions: Adherence to evidence-based performance measures for acute ischaemic stroke was suboptimal in China. There were various correlations among hospital individual performance measures. The hospital performance measures had no correlations with 30-day RSM rate and modest correlations with 1-year RSM rate.